Discovery of Brevibacterium predominating in fecal samples from three children with persistent diarrhea negative for common pathogens - Quy, Nguyen Thi; Khoa, Dao Trong; Nga, Pham Thi Thanh; Thuy, Phung Thi Bich; Hang, Nguyen Minh; Ha, Nguyen Thi Viet; Huyen, Do Thi (Vietnam Journal of Biotechnology, 2024)
Acute diarrhea is a common disease in children under 5 years old and can develop into persistent diarrhea, greatly affecting the children’s health. Although advanced techniques had been used to diagnose and detect common pathogens in hospitals, however, 40% of cases are negative for the pathogens. In this study, to investigate dominant bacteria in stool samples of three persistent-diarrheal children with unidentified pathogenic agents, the V3 and V68 regions of the 16S rRNA gene were amplified from fecal bacterial metagenomic DNA, separated on DGGE gel, and the dominant DNA bands were sequenced. As a result, the V3 and V68 regions of bacteria in persistent diarrheal children were less diverse and different from the corresponding DNA bands of the indicator strains. Sequence analysis and similarity comparison of six DNA bands of V3 regions and seven DNA bands of V68 regions showed that two V3 sequences (of 160 bp) derived from two samples were novel and did not match any genes from the non-redundant database, but they shared 93.75% similarity to each other. The four V3 sequences left derived from all three samples were the most similar (94.53-100%) with the corresponding genes of Brevibacterium. Six of the seven V68 sequences derived from dominant DNA bands of all three samples were the most similar (from 99.4% to 100%) to the corresponding genes of referent strains belonging to the genus Enterococcus. In sample D3, a sequence of the V68 region possessed 100% identity to the E. faecalis ATCC 19433 strain. This is the first study report that Brevibacterium was the dominant bacteria in the gastrointestinal microflora of children with persistent diarrhea although the bacterial genus has been reported to cause dangerous diseases in humans with immunodeficiency.